Nail gun injury to the median nerve: A barbed issue - S. Chintapalli; E. Phoenix; S. Cullen; R. Dolan (Trauma Case Reports)
Nail gun injuries to the hand are an increasingly common encounter amongst those in the construction injury and a frequent presentation to the emergency department. Despite their frequency, nail gun injuries rarely involve significant structural injury.We present a rare case of severe injury by a barbed nail to the median nerve requiring surgical exploration.At our latest follow up 14 months post-operatively, the patient had ongoing sensory and motor deficits, cold intolerance and reduced proprioception and range of motion at the index finger. Continued hand therapy resulted in improved range of motion and desensitization. A systematic literature search has revealed no other reported cases of median nerve injury by nail gun.